Persepsi masyarakat Tentang Fenomena Penggunaan Pengeras Suara dengan Volume Keras Terhadap Kenyamanan Berkehidupan Sosial (Studi Kasus: Desa Mergayu, Kecamatan Bandung, Kabupaten Tulungagung) - Finda Rahmatul Lail (The Indonesian Journal of Social Studies, 2023)
This study aims to find out, analyze the public’s perception of neighboring behavior using loudspeakers with hard volume in Mergayu Village, Bandung District, Tulungagung Regency. The method used in this study is a qualitative descriptive method with data collection that the researcher conducts through observation, and interviews. Meanwhile, data analysis techniques use a data analysis approach, namely data collection, data reduction, display data, and conslusion drawing. The selection of informants based on prposive sampling and informants in this study was 5 people. The results of this study show that the cognitive perception of the people of Mergayu Village towards the phenomenon of music suits with loud volumes gives a negative view and confidence, that the volume of music suits must be adjusted as needed 55 db (decibels). The affective perception of society with its foundation prohibits musical suits with loud volumes. The conative perception of the public is that there are those who act in protest regarding the phenomenon of musical suits with loud volumes. The reality of the people of Mergayu Village consists of social variety with different daily activities and beliefs that continue to strive to realize the comfort of social living.